Management of Adult Dengue Shock Syndrome Patients Not Improving with DEAG Guidelines Based Therapy - Muhammad Khurram ,Muhammad Faheem , Faisal Masood , Shahzad Manzoor , Muhammad Mujeeb Khan , Najaf Masood ,Muhammad Umar (Journal of Rawalpindi Medical College, 2016)
Background: Dengue Expert Advisory Group (DEAG) guidelines are used for management of dengue patients in our scenario. It was observed in last consecutive dengue epidemics at Rawalpindi that some of the dengue shock syndrome (DSS) patients don’t improve unless modifications in DEAG guidelines are made. This study was conducted to evaluate modified DEAG management guidelines in DSS patients with decompensated shock who were not improving with treatment based on standard DEAG guidelines. Methods: This quasi experimental study was conducted at Dengue Units of Hospitals attached with Rawalpindi Medical College during Rawalpindi dengue epidemic 2015. Dengue Shock Syndrome (DSS) patients who were not improving with DEAG guidelines based treatment, were managed as per modified treatment plan i.e., continuing with colloid or blood depending on HCT in tapering way for initial few hours after hemodynamic stabilization is achieved. Outcome was recorded in terms of improvement/recovery and mortality. Poor outcome (mortality was correlated with mean age, gender, primary or secondary dengue infection, presence of additional illnesses and mean duration of hospital stay by Chi2 and t test wherever relevant. Results: Seventeen patients were included in the study. 64.7% were female. Mean patient age was 31.29±9.56 years. Thirteen patients (76.47%) recovered and were discharged. Four patients (23.52%) expired. Poor outcome had statistically significant association with presence of additional illnesses and shorter duration of hospital stay (p value <0.05). Conclusion: Modification in DEAG treatment plan lead to better outcome in majority of DSS patients who did not improve with DEAG standard management.